A Study In Level Of Mitigation Strategies For Emissions Of Greenhouse Gases. - Chan, Ken Ming (2006)
In this project, a control model has been developed to estimates the CO2 emissions from 1998 to 2012 accordingly to the Kyoto Protocol. The Kyoto Protocol called for each developed (Annex I) country to reduce annual emissions in the period 2008-2012 to about 5% below what they had been in 1990.